3D-printed porous bed structures. (November 2017) - Fee, Conan
Highlights: The potential of additive manufacturing to create porous media is described. Experimental validation of computational fluid dynamics studies examples are given. Opportunities and challenges for production of designed porous media are presented. Abstract : The potential for the use of additive manufacturing ('3D printing') to fabricate finely controlled mesostructures presents new opportunities for chemical engineers to refresh their approach to the design of unit operations involving porous beds. Having control over the size, shape, position and orientation of every element within a porous bed, along with the growing availability of materials that can be printed and functionalised, means that we no longer have to rely upon random packing of individual particles to achieve intimate fluid–solid contact. New, fresh approaches to the design of not only the solid-phase but also the fluid-phase geometries within a porous bed are now possible, offering the opportunity to increase process efficiency and to customise porous beds for particular applications. This paper outlines some of the opportunities and challenges presented to what, until now, has been considered to be a relatively mature area of chemical engineering science and design, by the rapidly emerging area of additive manufacturing.